Truly eccentric – II. When can two circular planets mimic a single eccentric orbit?. Issue 3 (23rd January 2019) - Wittenmyer, Robert A; Bergmann, Christoph; Horner, Jonathan; Clark, Jake; Kane, Stephen R
Abstract: When, in the course of searching for exoplanets, sparse sampling and noisy data make it necessary to disentangle possible solutions to the observations, one must consider the possibility that what appears to be a single eccentric Keplerian signal may in reality be attributed to two planets in near-circular orbits. There is precedent in the literature for such outcomes, whereby further data or new analysis techniques reveal hitherto occulted signals. Here, we perform suites of simulations to explore the range of possible two-planet configurations that can result in such confusion. We find that a single Keplerian orbit with e ≳ 0.5 can virtually never be mimicked by such deceptive system architectures. This result adds credibility to the most eccentric planets that have been found to date, and suggests that it could well be worth revisiting the catalogue of moderately eccentric 'confirmed' exoplanets in the coming years, as more data become available, to determine whether any such deceptive couplets are hidden in the observational data.